Reduction of microvoids in composite laminates fabricated by bladder assisted composite manufacturing (BACM). Issue 2 (15th September 2014) - Anderson, J.P.; Altan, M.C.
Abstract : Bladder Assisted Composite Manufacturing (BACM) is a recently developed out‐of‐autoclave process designed to fabricate geometrically complex, hollow composite parts. This paper assesses the ability of three new BACM process variations to fabricate parts with high fiber and low void contents. This was achieved by fabricating 4‐ply cylinders from a carbon/epoxy prepreg at cure pressures of 207 and 483 kPa. The fiber/void content, mechanical properties, and energy consumed during the curing of the cylinders are investigated and compared to the original BACM process. The fiber content of the cylinders were observed to be dependent on both bladder pressure and BACM variation used, reaching a maximum fiber content of 66% which is 5% greater than that obtained by the original BACM process. The elastic moduli and failure strength results for the cylinders were found to increase with fiber content and showed no preference to any of the studied BACM process variations. In addition, the void content of the cylinders were reduced by 94% with the utilization of a porous bleeder fabric when compared to the original BACM process. POLYM. COMPOS., 37:561–572, 2016. © 2014 Society of Plastics Engineers